Integrodifferential relations in linear elasticity - Kostin, G. V. (De Gruyter studies in mathematical physics ;, 2012)
This work treats the elasticity of deformed bodies, including the resulting interior stresses and displacements. It also takes into account that some of constitutive relations can be considered in a weak form. To discuss this problem properly, the method of integrodifferential relations is used, and an advanced numerical technique for stress-strain analysis is presented and evaluated using various discretization techniques. The methods presented in this book are of importance for almost all elasticity problems in materials science and mechanical engineering.